Algorithms for scheduling projects with generalized precedence relations - DE REYCK, Bert (Institutional Knowledge at Singapore Management University, 1999)
The problem of scheduling projects under various types of resource constraints constitutes an important and challenging problem which has received increasing attention during the past several years. The bulk of the models and procedures designed for coping with these problem types aim at scheduling project activities to minimize the project duration subject to constant availability constraints on the required set of resources and precedence constraints that indicate that activities can only be started when all of their predecessors have already been finished. However, real-life project scheduling applications often involve more complicated types of precedence relations such as arbitrary minimal and maximal time lags between the starting and completion times of the activities, and require more sophisticated regular and nonregular objective functions. Over the past few years, considerable progress has been made in the use of exact solution procedures for this problem type and its variants. We will review the fundamental logic and report new computational experience with solution procedures for optimally solving resource-constrained project scheduling problems in which such generalized precedence relations and objective functions can be explicitly considered.